2011
DOI: 10.1007/s00256-011-1137-z
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on femoroacetabular impingement

Abstract: Although Smith-Petersen described impingement of the native hip in 1936 [1], the success of replacement arthroplasty of the hip dominated the orthopaedic literature until the early contemporary reports of femoroacetabular impingement (FAI) at the turn of the millennium [2]. Subsequently, an exponential increase in interest in the subject has occurred, as demonstrated by the annual number of Pubmed hits for FAI, which reached 168 in 2010 alone. This interest is perhaps not surprising when one considers that FAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Surgical techniques for treating symptomatic FAI often include bone reshaping, management of chondral defects through debridement and microfracture, and debridement and repair of damaged labral tissue. However, arthroscopic surgery for FAI is relatively new and multiple opinions exist over the techniques and post‐operative physical therapy regimens that should be prescribed for each individual . Surgical outcomes are generally reported in terms of pain reduction, improved femoral head and acetabular geometry, and better clinical passive ROM .…”
mentioning
confidence: 99%
“…Surgical techniques for treating symptomatic FAI often include bone reshaping, management of chondral defects through debridement and microfracture, and debridement and repair of damaged labral tissue. However, arthroscopic surgery for FAI is relatively new and multiple opinions exist over the techniques and post‐operative physical therapy regimens that should be prescribed for each individual . Surgical outcomes are generally reported in terms of pain reduction, improved femoral head and acetabular geometry, and better clinical passive ROM .…”
mentioning
confidence: 99%
“…The degree of acetabular overcoverage is usually determined in reference to the pelvis in neutral position [33], but the pelvis is often not positioned neutrally in the standing position and during gait [36,[39][40][41]. The pelvic tilt increases or reduces the degree of acetabular overcoverage (Fig.…”
Section: Atypical Hip Impingementmentioning
confidence: 98%
“…However, it has been suggested that correcting an increased lumbar lordosis, strengthening of core muscles, or physical therapy could be part of a nonsurgical treatment in mild cases of patients with FAI by normalizing pelvic tilt [41,[46][47][48].…”
Section: Atypical Hip Impingementmentioning
confidence: 99%
“…12 The alpha angle is often used as a quantitative measurement of cam deformity, although its accuracy and diagnostic value have been questioned. [25][26][27] Subjective assessment of alpha angles has been judged as suboptimal in one study, except where the observer was confident of a marked bony abnormality. 28 The alpha angle was first proposed on MRI, with a pathological threshold value of 50° for both genders.…”
Section: Alpha Angle (°) On Frog-leg View Alpha Angle (°) On Ap Viewmentioning
confidence: 99%